Use of a yeast site-specific recombinase to produce female germline chimeras in Drosophila. - Chou, T.B.; Perrimon, N. (Genetics, 1992)
We describe an efficient method for generating female germline mosaics by inducing site-specific homologous mitotic recombination with a yeast recombinase (FLP) which is driven by a heat shock promoter. These germline mosaics are produced in flies heterozygous for the agametic, germline-dependent, dominant female sterile (DFS) mutation ovoD1, where only flies possessing germline clones are able to lay eggs. This method, the "FLP-DFS" technique, is very efficient because more than 90% of females with germline clones can be recovered. We show that this heat-inducible, site-specific mitotic recombination system does not affect viability and that the germline clones recovered are physiologically the same as those created by X-ray induced mitotic recombination. We describe the parameters of FLP-recombinase induced germline mitotic recombination and the use of the "FLP-DFS" technique to analyze the maternal effect of X-linked zygotic lethal mutations.